EcoMoronene: A local wisdom-based conservation learning model to address environmental degradation - Dewi, Chitra; Rahmadani, Nanang; Syahrir, Muhammad; Rahayaan, Jones Juan Dany; Nurjannah, Fathinah (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Environmental degradation caused by artisanal and small-scale gold mining in Bombana, Southeast Sulawesi, presents serious ecological and public health risks, including mercury and arsenic contamination. Previous studies highlight the importance of culturally grounded education in promoting sustainable conservation practices, yet few have tested the validity and reliability of instruments designed to measure learning outcomes in this context. This study aimed to evaluate the effectiveness of the EcoMoronene Initiative, an educational model that integrates Moronene local wisdom—such as sacred forest stewardship, water resource protection, and biodiversity conservation—into youth-based conservation learning. Methods: A quasi-experimental pre–post control design was applied with 80 participants divided equally into an experimental group, which received the EcoMoronene module, and a control group, which followed regular activities. Data were collected through a knowledge–attitude questionnaire, a conservation behavior rubric, and observation, then analyzed using descriptive statistics, t-tests, Cronbach’s alpha, and confirmatory factor analysis. Findings: Findings revealed significant improvements in the experimental group’s knowledge (mean increase from 6.2 to 8.5, p = 0.001), alongside positive shifts in attitudes and behaviors, while the control group showed negligible changes. Reliability analysis confirmed strong internal consistency (α = 0.86 for the Knowledge–Attitude questionnaire; α = 0.83 for the Behavior rubric), and validity was supported by good model fit indices (χ²/df = 1.8, CFI = 0.94, RMSEA = 0.05). These results demonstrate that embedding local wisdom into conservation education enhances motivation, cultural identity, and pro-environmental actions among youth. Conclusion: research study that distinguish it from previous work. It includes unique contributions, new methods, or findings that have not been explored before in the field. Novelty/Originality of this article: This study uniquely integrates Moronene local wisdom into conservation education, validating reliable instruments and demonstrating significant improvements in youth knowledge, attitudes, and behaviors, distinguishing it from prior research in environmental education.